Penerapan Quantum Learning Berbantuan Peta Konsep untuk Meningkatkan Keterampilan Membaca Pemahaman dan Prestasi Belajar Bahasa Indonesia - Wibowo, Ervin Nurcahyo; Ernawati, Asih (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study aims to improve students reading comprehension skills and learning achievement through Quantum Learning model assisted by concept maps in Indonesian language learning for fifth grade students. This classroom action research was conducted in two cycles each consisting of two meetings with a total of 19 students as research subjects. Data were primarily collected from observation sheets, evaluation sheets and documentation. The results of this study showed a gradual increase in reading comprehension skills and student achievement. In cycle I, reading comprehension skills reached a level of completeness of 57.89% (sufficient), then in cycle II the level of completeness reached 86,84% (very good). Learning achievement has increased gradually as well, in cycle I the completion rate was 52,63% (enough) and in cycle II the completion rate reached 84,21% (very good). This study shows that the application of Quantum Learning model assisted by concept maps can improve reading comprehension skills and learning achievement of fifth grade students.